(untitled) - Tamarin, Robert H. (Dubuque, IA, 1996)
This tex provides a balanced treatment of the major areas of genetics in order to prepare the student for upper-level courses and to help share in the exitement of research. Most readers of this text will have had some background in cell biology and organic chemistry. For an understanding of the conceps in this text, however, the motivated student will need to have completed only an introductory biology course and have had some chemistry and algebra in high school.
Keywords: Genetics,Di truyền học